Use of a MAMA-PCR Method to detect gyrA Mutations in Nalidixic Acid-Resistant Clinical Isolates of Escherichia coli - A Karami; KH Naghavi; R Sorouri; R Ranjbar; A Khalilpour (Tehran University of Medical Sciences, 2008)
Background: Enterobacteriaceae are a large group of bacteria widely distributed in nature. Escherichia coli is the most common cause of urinary tract infection. Two amino acid substitutions, in GyrA, are commonly responsible for quinolone resistance in E. coli. The aim of this study was molecular survey of nalidixic acid resistance E.coli isolated from patients in the codones of 83 and 87 gyrA genes.Methods: During 5 months (January to June 2005) of Molecular Survey of Nalidixic Acid Resistance, one hundred and twenty-one E. coli isolates from urine samples of patients referred to clinical laboratory of Baqiyatallah Hospital were cultured. Differential tests were done for diagnosis of E.coli. An economical and time-efficient mismatch amplification mutation assay (MAMA) PCR was developed to detect mutations in the chromosomal gyrA gene causing these substitutions.Results: In nalidixic acid antibiogram test, 55 cases (45.5%) were sensitive, 63 cases (52%) were resistant and 3 cases (2.5%) were intermediate. Results of PCR and MIC were similar to antibiogram. There was not any mutation in the sensitive samples but there were performed five mutations on the 85, 81, 107, 97 and 87 codones of resistance samples. The codone number 87s mutation is one of the main mutations of nalidixic acid resistance.Conclusion: Depending on results of this study and comparison with other studies, trend of resistance of E.coli is increasing. Therefore, we recommend control of antibiotic misusage and application of MIC and PCR tests (if possible) prior to treatment for suitable selection of antibiotic and prevention of microbial resistance.